Pemberdayaan Masyarakat Desa Bunde dalam Meningkatkan Kesehatan Reproduksi dan Seksualitas melalui Edukasi Kebidanan - Fadhilah, Iin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Reproductive and sexual health are crucial aspects of achieving a healthy, productive, and prosperous quality of life. However, many rural communities still have limited knowledge about reproductive health, putting them at risk of problems such as unwanted pregnancies, sexually transmitted infections, and a lack of awareness of the importance of maintaining reproductive health. This community service activity was conducted in Bunde Village with the aim of increasing public understanding, particularly among adolescents and couples of childbearing age, about reproductive health and sexuality through a midwifery education approach. The methods used were interactive lectures, group discussions, and the distribution of educational media in the form of leaflets. The results of the activity showed a 70% increase in participants' knowledge after the education, as well as a positive change in attitudes toward maintaining reproductive health. This activity also successfully encouraged community participation to be more open in discussing reproductive health issues, which have previously been considered taboo. Midwifery education has proven effective as a means of community empowerment in increasing awareness and concern for reproductive health and sexuality.